-7s-9+11s=-5+4s-4

Simple and best practice solution for -7s-9+11s=-5+4s-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7s-9+11s=-5+4s-4 equation:


Simplifying
-7s + -9 + 11s = -5 + 4s + -4

Reorder the terms:
-9 + -7s + 11s = -5 + 4s + -4

Combine like terms: -7s + 11s = 4s
-9 + 4s = -5 + 4s + -4

Reorder the terms:
-9 + 4s = -5 + -4 + 4s

Combine like terms: -5 + -4 = -9
-9 + 4s = -9 + 4s

Add '9' to each side of the equation.
-9 + 9 + 4s = -9 + 9 + 4s

Combine like terms: -9 + 9 = 0
0 + 4s = -9 + 9 + 4s
4s = -9 + 9 + 4s

Combine like terms: -9 + 9 = 0
4s = 0 + 4s
4s = 4s

Add '-4s' to each side of the equation.
4s + -4s = 4s + -4s

Combine like terms: 4s + -4s = 0
0 = 4s + -4s

Combine like terms: 4s + -4s = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| X-9y=81 | | 3x+2+x+-6=25 | | 23-11=35c | | 2a+16= | | 3(n+7)=21 | | 2n+3-4n-10=1-3n | | 6m+1=-3 | | -9=27-11b-13b | | -28+p=7(p-10) | | Y^2-39y-42=0 | | 5.50c+8=35 | | 5(x-1)=x+25 | | 16(2-w)+11w=-13 | | -3(2x-3)=3(x-1) | | X+6=567+3-2 | | a+5+2a=5+3a | | 4x+3y=110 | | 3-w-(7w+12)=2(w-3) | | 4x=6z+76 | | 7*7-(8-2)= | | 6+4x=4x-5 | | 2(-x)-4+4x=x+5 | | 13+3x=5x-5 | | 9x+4x=2x+3 | | 13-(4-k)=5k+10-7 | | 37-X=14 | | 48-6x=4x-2 | | 8-g= | | X+150=.75(x+150) | | 3(4x-9)+12=9 | | 5t-7=5t | | 2a+14=-2(-a-3) |

Equations solver categories